COVID-19 vertical transmission from mothers to neonates: A systematic review and meta-analysis of 204 studies - Fatemeh Movahed; Fariba Haji Hosseini; Afshin Heidari; Masoud Dehbozorgi; Mina Ataei; Farnaz Vahidi; Romina Abyaneh; Bahar Bajelan; Mahmood Bakhtiyari; Arman Shafiee (Journal of Infection and Public Health, 2025)
This study estimates the prevalence of vertical transmission of SARS-CoV-2 and identifies risk factors for mother-to-neonate transmission. A comprehensive search of PubMed, Scopus, and Web of Science up to May 2024 identified 204 observational studies, out of 28,543 records, that included neonates with confirmed SARS-CoV-2 detection via RT-PCR. The overall vertical transmission rate was 4 % (95 % CI: 4 %–5 %), with notable heterogeneity (I² = 75 %). Transmission varied based on delivery method, income classification, and region, being higher in lower-income areas and cesarean deliveries. Maternal SARS-CoV-2 detection in breast milk was rare. Neonatal SARS-CoV-2-specific IgG antibodies were frequently detected, while IgM antibodies were less common. The findings highlight the infrequency of vertical transmission but underline disparities in healthcare practices. Further high-quality studies, especially in low-income regions, are essential for a deeper understanding of vertical transmission dynamics in diverse clinical settings.